2018
DOI: 10.1017/s1355617718000759
|View full text |Cite
|
Sign up to set email alerts
|

Automated Indices of Clustering and Switching of Semantic Verbal Fluency in Parkinson’s Disease

Abstract: Objectives: Deficits in semantic verbal fluency (SVF) can stem from dysfunction of an executive control system and/or of semantic knowledge. Previous analyses of SVF responses were devised to characterize these two components including switching and mean cluster size (MCS) indices, but these rely on subjective experimenter-based assessment of the words’ relatedness. To address this limitation, computational data-driven SVF indices have been developed. Our aim is to assess the validity and usefulness of these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
4
8
1
Order By: Relevance
“…The Troyer method relies heavily on experimenters' subjective judgment of semantic relatedness and cluster segmentation. Farzanfar et al compared an automated computational assessment with the traditional experimenter-based assessment of semantic fluency data from patients with PD [ 8 ]. In the computational assessment, each word was represented as a vector in a semantic space derived from corpora.…”
Section: Introductionmentioning
confidence: 99%
“…The Troyer method relies heavily on experimenters' subjective judgment of semantic relatedness and cluster segmentation. Farzanfar et al compared an automated computational assessment with the traditional experimenter-based assessment of semantic fluency data from patients with PD [ 8 ]. In the computational assessment, each word was represented as a vector in a semantic space derived from corpora.…”
Section: Introductionmentioning
confidence: 99%
“…After the identification of word clusters, characteristics such as the mean cluster size and number of switches between clusters are calculated. Several studies suggested that the size of clusters is associated with language functions [10,14,16], whereas the number of switches is more strongly associated with executive functions [10,17]. Other authors, however, obtained conflicting results [12,17,18], and some studies found the cluster size and number of clusters to be highly correlated, which means that they might not represent independent parameters at all [7,17,19].…”
Section: Clusters In the Verbal Fluency Task Transcriptmentioning
confidence: 99%
“…Technology may provide opportunity for clarification on the subtle components of performance in verbal fluency tasks and on the value of switching and clustering as reliable indices of differential performance between normal and pathological aging conditions. For example, Farzanfar et al (2018) used an automated computational approach to yield switching, mean cluster size and cumulative relatedness indices in individuals with cognitive decline in Parkinson's disease. These researchers found that automated switching indices showed evidence of concurrent and construct validity, characterized individual difference in advanced PD, and outperformed the experimenter-dependent index in predicting MCI associated to PD.…”
Section: Verbal Fluency Tasksmentioning
confidence: 99%